Non-specific Low Back Pain and Postural Control During Quiet Standing—A Systematic Review - Koch, Cathrin; Hänsel, Frank (Frontiers in Psychology, 2019)
Background: There is a great number of people who require treatment for non-specific low back pain (LBP) yet the causes are still unclear. One proposed cause for LBP is impaired motor control and more specific an impaired postural control. Objective: The purpose of this review is to provide an overview of postural control parameter differences in persons with and without non-specific LBP during quite standing. Methods: A literature search in five databases from January 2000 until January 2018 was performed and was followed by a hand search. Twenty-one articles comparing healthy adults and adults with non-specific LBP in neuromuscular and/or biomechanical parameters during bipedal stance without external perturbation in lab studies were examined. Data extraction and quality assessment were independently performed by two persons. Factors such as study population, outcome measures and results were extracted from the articles and included in this analysis. Results: The results show that persons with and without non-specific LBP differed in several parameters of postural control such as the center of pressure displacement, postural control strategy, and muscle activation patterns. Conclusion: While the results show that none of the parameters alone lead to significant effects, the combination of neuromuscular and biomechanical parameters was associated with the impairment of postural control in individuals with LBP during standing. Since the studies included in this analysis used different methodological procedures a replication of these studies with standardized procedures is imperative for the acquisition of more conclusive evidence on the differences in postural control during standing.